2007
DOI: 10.1007/s11695-007-9225-9
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Producing Infection of the Spleen in a Super-Super-Obese Patient

Abstract: Gas-producing bacteria are known to selectively colonize a variety of abdominal viscera, but gas-producing infection limited to the spleen until now has not been reported. A gas-producing (emphysematous) infection of the spleen was diagnosed in a super-super-obese diabetic patient with abdominal pain and signs of sepsis. The patient presented a serious diagnostic challenge because massive abdominal obesity did not enable her to pass through the aperture of a standard computerized tomography unit. Therapeutic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…[21][22][23][24][25][26] Either in human or veterinary medicine, the most common malignant causes of intraparenchymal gas gangrene are primary abscesses or infected neoplasms both due to gas-producing bacteria. 7,[13][14][15][27][28][29][30] Based on our review of the literature, the cases of intraparenchymal splenic gas described in veterinary medicine have been caused by air embolism secondary to visceral torsion or infarction. [16][17][18][19] In one canine patient, Clostridium spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[21][22][23][24][25][26] Either in human or veterinary medicine, the most common malignant causes of intraparenchymal gas gangrene are primary abscesses or infected neoplasms both due to gas-producing bacteria. 7,[13][14][15][27][28][29][30] Based on our review of the literature, the cases of intraparenchymal splenic gas described in veterinary medicine have been caused by air embolism secondary to visceral torsion or infarction. [16][17][18][19] In one canine patient, Clostridium spp.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Spontaneous emphysematous splenitis, or splenic gas gangrene, is considered a severe and life-threatening condition in humans. [5][6][7][8][9][10][11][12][13] However, at the time of this study, no published reports describing this condition in veterinary patients were found. Spontaneous emphysematous splenitis in humans is usually defined as the presence of septic and gaseous areas within the splenic parenchyma produced by anaerobic pathogens.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, direct invasion of the spleen by means of fistulization of penetrating gastric ulcers, colonic adenocarcinoma at the splenic flexure, or distal pancreatic malignant disease has also been implicated in certain rare instances [5][6] and can produce the gas-forming necrosis of the spleen demonstrated in the case of this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment may include CT-guided percutaneous aspiration for unilocular collections or splenectomy for more diffuse infections, as in the case with this patient. For some patients that are not candidates for such therapies, treatment with long-standing antibiotics alone has also been described [5].…”
Section: Discussionmentioning
confidence: 99%